Aplikasi Virtual Tourism Promosi Kampung Tematik Kota Malang berbasis Web VR 360 - Danar Hikmah Krismanto; Herman Tolle (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Thematic village is a place administratively under a sub-district that has both a social and economic potential. However, at this time the spread of the Covid 19 pandemic virus outbreak caused the closing down of almost all thematic village. Based on these problems, in this research a virtual reality (VR) application for promotion of thematic villages by using web VR 360. This application is developed using Agile software development life cycle. The aplication is divided into 2 part, they are VR applications for users and admin system for admins to manage data VR. The implementation of virtual reality applications uses the Aframe framework and the admin system uses the Laravel framework. System testing is done using blackbox testing to test functional requirements and use usability testing to test non-functional requirements. The results fungsional testing is all functionality requirements are valid. The results non-functional testing using usability testing for VR applications got an average System Usability Testing (SUS) score of 75.5 and for the admin system it got an average SUS score of 77. It can be concluded that the system being developed is good for use.